The assessment of the longitudinal arch of the foot in deaf and hearing children aged 9 to 11 years Hodnocení podélné klenby nohy u hluchých a slyšících dětí ve věku od 9 do 11 let - Mirosław Górny; Marzena Wiernicka; Ewa Kamińska (Acta Universitatis Palackianae Olomucensis. Gymnica, 2009)
The aim of the study was to establish the condition of the foot arch in deaf and hearing children and to determine whether there are differences in the foot arch between children with impaired hearing and healthy children aged 9–11 years. A group of 19 deaf children and 33 hearing children, including 23 girls and 29 boys aged 9 to 11 years were studied. Their average age was 9.9 years. The examination of the longitudinal arch of the feet was carried out in an nonloaded (in a sitting position) and in a loaded (standing) position, using a Podoskop (POSMED, Poland). In the preparation of impressions of the soles of the feet, a line method according to Wejsflog was used with the specification of an index of the longitudinal arch of the foot. It was noted that there was a statistically significant difference between the arch of the left and the right feet in loading in healthy children (p < 0.05). However, no statistically significant differences were noted between the studied groups of children in terms of the indicator of the arch of the foot in both an unloaded and loaded posture. It was noted however, that the condition of the arch of the foot in deaf children was characterised by a lower effectiveness of the muscular and ligament systems, which was confirmed by the values of the foot parameters of deaf children. The results of the Wejsflog index indicate that in deaf children a typical area of variables (the right foot in loading 20.55–39.85) was greater than in healthy children (the right foot in loading 17.05–34.75). Moreover, in both groups of girls greater differences were noted in the degree of foot arching than in boys. This confirms the tendency to generally a more labile body posture in girls and in the muscular and ligament system of the feet. In conclusion, no statistically significant differences were noted between the studied groups of children in terms of the index of the arch of the foot in both a loaded and an unloaded posture. Cílem studie bylo zjistit stav klenby nohy u hluchých a slyšících dětí a určit, zda existují rozdíly mezi klenbou nohy u dětí s poškozením sluchu a u zdravých dětí ve věku 9–11 let. Studie proběhla na skupině 19 hluchých dětí a 33 slyšících dětí, z nichž bylo 23 dívek a 29 chlapců ve věku 9 až 11 let. Jejich průměrný věk byl 9,9 let. Vyšetření podélné klenby nohy bylo provedeno v poloze nezatížené (v sedě) a zatížené (ve stoje), za použití podoskopu (POSMED, Polsko). Při přípravě otisků chodidel byla použita lineární metoda dle Wejsfloga se specifikací ukazatele podélné klenby nohy. Byl zjištěn statisticky významný rozdíl mezi klenbou levé a pravé nohy v zatížené poloze u zdravých dětí (p < 0,05). Nebyly ovšem zjištěny žádné statisticky významné rozdíly mezi zkoumanými skupinami dětí, pokud jde o ukazatele klenby v nezatížené i zatížené poloze. Nicméně bylo zjištěno, že stav klenby nohy u hluchých dětí byl charakterizován nižší efektivitou svalového a vazivového systému, což potvrdily hodnoty parametrů nohou u hluchých dětí. Výsledky Wejsflogova ukazatele svědčí o tom, že u hluchých dětí byla typická oblast proměnných (pravá noha v zatíženém stavu 20,55–39,85) větší než u zdravých dětí (pravá noha v zatíženém stavu 17,05–34,75). Navíc byly u obou skupin dívek zjištěny větší rozdíly ve stupni klenutí nohy než u chlapců. Toto potvrzuje tendenci k všeobecně labilnějšímu držení těla u dívek a ve svalovém a vazivovém systému nohy. Závěr: nebyly zjištěny žádné statisticky významné rozdíly mezi zkoumanými skupinami dětí, pokud jde o ukazatele klenby v nezatížené i zatížené poloze.